Uric Acid as a Significant Risk Factor for Hypertension Severity, Unlike Lipid Profiles - Triastuti, N Juni; Erna Herawati; Sintowati, Retno; Faizah , Ariyani; Anisa Putri, Dede; Amalia, Raisya; Amalia, Regal; Embiysne , Viamell; Kusuma Ningrum, Sukma; Basuki, Sri Wahyu (Fakultas Kedokteran Universitas Brawijaya, 2026)
Hypertension remains a global health problem experienced by the world's population, as evidenced by its high prevalence and mortality rate. For 90-95% of hypertension sufferers, the cause of hypertension was reported as unknown. However, there are several risk factors associated with hypertension, notably genetic factors, age, gender, diabetes mellitus, lifestyle and diet, as well as lipid and uric acid profiles. This study aims to analyze uric acid and propyl lipid levels with hypertension severity. The study employed a quantitative research design. Data were collected through purposive sampling, yielding a total sample of 110 participants. The dataset was subsequently analyzed using logistic regression test. Based on the logistic regression statistical test, the following results were obtained: uric acid levels (p-value <0.05; OR >1; CI did not exceed 1); triglyceride levels (p-value >0.05; OR >1; CI exceeded 1); total cholesterol levels (p-value >0.05; OR <1; CI exceeded 1); and low-density lipoprotein levels (p-value >0.05; OR >1; CI exceeded 1). Thus, it can be concluded that abnormal uric acid levels significantly affect the severity of hypertension. Abnormal triglyceride levels and low-density lipoprotein levels show a tendency to increase the risk of hypertension severity but are not yet statistically significant. There is a tendency for abnormal total cholesterol levels to be less risky for severe hypertension compared to normal total cholesterol levels, but this disparity is not significant. Nevertheless, the probability of all variables with abnormal levels possessed a 12% risk of hypertension severity remains.